Comparison of control oocytes and oocyte with mild and dark severe coarse granules in the perivitelline space: insights on IVF-ICSI cycle outcomes: a retrospective cohort analysis - Anand, Papitha P.; Mariappan, Scindiya; Ramakrishnan, Sujatha (International Journal of Research in Medical Sciences, 2025)
Background: Coarse granules in the perivitelline space (PVS) have been associated with impaired oocyte quality and reduced success rates in assisted reproductive technologies. However, their precise impact on IVF-ICSI cycle outcomes remains unclear. This study aims to evaluate the correlation between PVS granularity and embryological as well as clinical outcomes. Methods: This retrospective cohort study analyzed 161 women undergoing IVF/ICSI cycles at Nova IVF Fertility Centre, Madurai, between January 2022 and March 2025. Oocytes (n=2300) were classified into three groups based on the presence of PVS granules: Group A (Control oocytes), Group B (Moderate granules), and Group C (Dark severe granules). Statistical analyses assessed differences in oocyte maturation, fertilization, embryo development, implantation, and live birth rates. Results: Group C exhibited significantly higher AMH levels (p<0.008) and increased oocyte retrieval rates (p<0.039). However, fertilization efficiency, cleavage rates, and implantation rates were significantly lower in both Group B and Group C. ROC analysis identified MII oocytes (AUC=0.683) and fertilization rates (AUC=0.674) as the strongest predictors of implantation success. The clinical pregnancy rate was highest in Group A (79.3%) and lowest in Group C (40.2%) (p<0.000). Despite a comparable live birth rate between Groups A and C, ongoing pregnancy rates were significantly lower in Group C (13.4%). Conclusions: Dark severe granules in PVS negatively impacts oocyte competence and IVF success. Optimizing ovarian stimulation protocols and incorporating advanced embryo selection techniques may improve ART outcomes for patients with granular oocytes.